Metal composition and contamination assessment of urban roadway dusts on the Abu Dhabi-Liwa Highway, UAE - Al-Taani, Ahmed A.; Nazzal, Yousef; Howari, Fares M.; Iqbal, Jibran; Naseem, Muhammad; Sharma, Manish; Xavier, Cijo; Papandreou, Dimitrios; Maloukh, Lina; Ambika, Lakshmi; Ben Salem, Imen; Al Bsoul, Abeer; et al. (Frontiers in Environmental Science, 2023)
The metal composition of road deposited dust along Abu Dhabi-Liwa highway were investigated to provide insight into the contamination profile and levels of road dust. The average concentrations of metals decreased in the order Al (28668±4631 mg/kg)> Fe (21461±2594 mg/kg) > Mn (711.8±76.3 mg/kg) > Zn (210.6±51.6 mg/kg) > Cu (94.9±15.8 mg/kg) > Pb (83.6±5.3 mg/kg) > Cd (75.1±1.6 mg/kg) > Co (62.6±6.4 mg/kg) > As (4.7±2.9 mg/kg) > Ni (0.10± 0.19 mg/kg) > Cr (0.08±0.06 mg/kg). The spatial variations of metals suggest different sources and contributing factors for these metals, with most of dust metals are of mixed traffic and non-traffic origins. The contamination factor (CF) and enrichment factor (EF) showed identically the same order Cd> Pb> As> Zn> Co> Cu> Mn> Ni> Cr, whereas geoaccumulation index (Igeo) follows slightly different ranking Cd> Pb> Zn> Co> As> Cu> Mn> Ni> Cr. Based on EF and CF levels, roadway dusts are enriched in all metals, except for Ni and Cr. Similarly, the average Igeo values show differing rates of pollution for all metals except for Mn, Ni, and Cr. All pollution indicators suggest extreme pollution with Cd. The pollution loading index values showed sites 1-10 are generally polluted while sampling sites from 11 to 19 are unpolluted with decreasing pollution loadings. Dusts collected from both sides of highway were higher in metal content than those obtained from the central reservation area. This may be due to the prevailing southeast wind direction, resuspension of road dust and farmlands, among others. Soils bordering the highway showed high metals contents with potential consequences on the agricultural products.